Help-Seeking Behaviors as Cultural Capital: Cultural Guides and the Transition from High School to College among Low-Income First Generation Students. (28th June 2020) - Richards, Bedelia Nicola
Abstract: This article argues that educational institutions can transmit cultural capital in the form of help-seeking dispositions (feeling empowered to ask for and receive help) and specialized knowledge (information about how to gain access to resources) that can positively impact students' academic outcomes. Additionally, this article questions the perception that educational institutions function primarily as agents of social reproduction, by showing that institutional agents such as high school teachers and administrators can function as "cultural guides" to bolster students' opportunities for social mobility. Drawing on interviews with graduates of King and Chavez, two early college high schools which target low-income, first-generation college students, I find that King graduates were more strategic help-seekers and were more likely to use campus-based resources than their counterparts at Chavez, in part because their school's curriculum explicitly and systematically taught this skill. This article challenges the perception that teachers and administrators function exclusively as gatekeepers in educational institutions. Instead, the data presented show that these institutional agents can also function as "cultural guides" who transmit cultural capital in the form of help-seeking values and behaviors to students from economically marginalized communities; promoting their upward mobility.